Collaboration and Technology 16th International Conference, CRIWG 2010, Maastricht, The Netherlands, September 20-23, 2010. Proceedings - Kolfschoten, Gwendolyn; Herrmann, Thomas; Lukosch, Stephan; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the proceedings of the 16th Collaboration Researchers' International Working Group Conference on Collaboration and Technology, held in Maastricht, The Netherlands, in September 2010. The 27 revised papers presented were carefully reviewed and selected from numerous submissions. They are grouped into seven themes that represent current areas of interest in groupware research: knowledge elicitation, construction and structuring, collaboration and decision making, collaborative development, awareness, support for groupware design, social networking and mobile collaboration.
A Review of CRIWG Research -- Knowledge Elicitation, Construction and Structuring -- Supporting Collaborative Knowledge Creation in Mobile Working Scenarios -- Collaborative Conceptual Modeling Using an Ontology -- A Mobile Computer System to Support Collaborative Ethnography: An Approach to the Elicitation of Knowledge of Work Teams in Complex Environments -- A Method for Identification and Representation of Business Process Deviations -- Computer Supported Reflection of Good Practice -- Establishing On-Line Corporate Training in Distributed, Synchronous eCollaboration: A Field Study -- Decision Support -- Integrating Spatial Data and Decision Models in an E-Planning Tool -- Supporting the Decision Implementation Process -- A Framework and an Architecture for Context-Aware Group Recommendations -- Collaboration Support -- Concurrent Modeling in Early Phases of the Software Development Life Cycle -- The Integration of Collaborative Process Modeling and Electronic Brainstorming in Co-located Meetings -- Integrating Context-Enriched Explanations and Communication in an Adaptive Collaboration Environment -- A Tool for Training Students and Engineers in Global Software Development Practices -- Awareness -- Awareness Support in Global Software Development: A Systematic Review Based on the 3C Collaboration Model -- Awareness Checklist: Reviewing the Quality of Awareness Support in Collaborative Applications -- Supporting Asynchronous Workspace Awareness by Visualizing the Story Evolution in Collaborative Storytelling -- Groupware Design -- Dealing with Device Collaboration Rules for the PCSCW Model -- Enabling Collaboration Transparency with Computational Reflection -- Plasticity of Interaction Interfaces: The Study Case of a Collaborative Whiteboard -- Developing a Framework of Common Information Space (CIS): Grounded Theory Analysis of Airport CIS -- Social Networking -- The Mind$1 (Bs Eye on Personal Profiles: How to Inform Initial Trustworthiness Assessments in Virtual Project Teams -- Supporting Informal Interaction in a Hospital through Impromptu Social Networking -- Ambient Displays for Integrating Older Adults into Social Networking Sites -- Mobile Collaboration -- A Simple and Portable Command Post to Coordinate Search and Rescue Activities in Disaster Relief Efforts -- Digital Workbook: A Mobile Learning Environment to Support Collaborative Examinations -- Evaluating a Prototype for Geo-referenced Collaborative Psychotherapy with Mobile Devices.s
Keywords: Computer science; Computer Communication Networks; Software engineering; Database management; Data mining; Information storage and retrieval systems; Information systems; Computer Science; Software Engineering; Information Systems Applications (incl.Internet).; Information Storage and Retrieval; Database Management; Data Mining and Knowledge Discovery; Computer Communication Networks